2017
DOI: 10.2174/1567201813666160808111209
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble Complex of Curcumin with Cyclodextrins: Enhanced Physical Properties For Ocular Drug Delivery

Abstract: Based on these results, F11 was formulated as eye drops, which provide a promising once daily novel topical delivery of this naturally derived phytochemical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Reducing tear osmolality and increasing tear production are well recognized by clinical trials in patients with dry eye disease [Wojtowicz et al, 2011;Georgakopoulos et al, 2016;Deinema et al, 2017], but there is no evidence of its significant effect on meibum lipid composition [Wojtowicz et al, 2011]. Maria et al [2016] have reported a formulated eye drop for curcumin with more aqueous solubility properties named F11. The mechanism of action reported to be decreasing cytokines and inhibiting oxidative stress [Li et al, 2014].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing tear osmolality and increasing tear production are well recognized by clinical trials in patients with dry eye disease [Wojtowicz et al, 2011;Georgakopoulos et al, 2016;Deinema et al, 2017], but there is no evidence of its significant effect on meibum lipid composition [Wojtowicz et al, 2011]. Maria et al [2016] have reported a formulated eye drop for curcumin with more aqueous solubility properties named F11. The mechanism of action reported to be decreasing cytokines and inhibiting oxidative stress [Li et al, 2014].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
“…A topical form of omega-3 fatty acid has been used in combination with hyaluronic acid with a good outcome in the treatment of dry eye in the mouse model. This formulation is sustained-release ones [Maria et al, 2016] and seems interesting in the management of different inflammatory ocular surface diseases in SM-exposed patients, but it needs further studies on animals and clinical trials to approve the formulation. Essential fatty acids should be considered for routine use in SM-exposed victims.…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
“…Maria designed a water-soluble complex of curcumin with cyclodextrins to make eyedrop delivery possible [67]. In addition, nanoparticles, which have been extensively studied in recent years, are being used as novel drug delivery systems because of their characteristics including biodegradability, non-toxicity, and hydrophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…This natural hydrophobic polyphenol is proposed as an alternative treatment for dry eye disease [31]. Maria et al [32] have developed a formulated eye drop for curcumin with more aqueous solubility properties. This sustained-release drop may be appropriate for the management of different inflammatory ocular surface disorders encountered in sulfur mustard-exposed patients [32].…”
Section: Medical Managementsmentioning
confidence: 99%
“…Maria et al [32] have developed a formulated eye drop for curcumin with more aqueous solubility properties. This sustained-release drop may be appropriate for the management of different inflammatory ocular surface disorders encountered in sulfur mustard-exposed patients [32]. However, further animal studies and clinical trials are required to approve the efficacy of this formulation.…”
Section: Medical Managementsmentioning
confidence: 99%